Observation of Associated Near-Side and Away-Side Long-Range Correlations in $\sqrt{s_{NN}}$=5.02 TeV Proton-Lead Collisions with the ATLAS Detector - ATLAS collaboration (2925 authors) (2013)
Two-particle correlations in relative azimuthal angle ($Δ-φ$) and pseudorapidity ($Δ-η$) are measured in $\sqrt{s_{NN}}$ = 5.02 TeV p+Pb collisions using the ATLAS detector at the LHC. The measurements are performed using approximately 1 $μ b^{-1}$ of data as a function of $p_T$ and the transverse energy ($\sum E_T^{Pb}$) summed over 3.1 < $η$ < 4.9 in the direction of the Pb beam. The correlation function, constructed from charged particles, exhibits a long-range (2<|$Δ-η$|<5) near-side ($Δ-φ$ ~ 0) correlation that grows rapidly with increasing $\sum E_T^{Pb}$. A long-range away-side ($Δ-φ$ ~ pi) correlation, obtained by subtracting the expected contributions from recoiling dijets and other sources estimated using events with small $\sum E_T^{Pb}$, is found to match the near-side correlation in magnitude, shape (in $Δ-η$ and $Δ-φ$) and $\sum E_T^{Pb}$ dependence. The resultant $Δ-φ$ correlation is approximately symmetric about $π$/2, and is consistent with a cos(2$Δ-φ$) modulation for all $\sum E_T^{Pb}$ ranges and particle $p_T$. The amplitude of this modulation is comparable in magnitude and $p_T$ dependence to similar modulations observed in heavy-ion collisions, suggestive of final-state collective effects in high multiplicity events.